John and Elaine Steinbeck at Discove Cottage - Unnkown:::Creator:::::::::::: (Bruton, Somerset; England, 2022)
John and Elaine Steinbeck pose with visitor in front of Discove Cottage. They stayed here for most of 1959 when Steinbeck was researching and writing The Acts of King Arthur and his Noble Knights. Bruton, a place of considerable antiquity, is a small town in Somersetshire on the river Brue, about 117 miles from London. Original in safe.